The Clean and Healthy Living Behavior as an Effort to Prevent Diarrhea in the Community of Cemara Kembar Coastal Area - Wasiyem, Wasiyem; Pane, Deswita Amelia Putri; Unzila, Fitri; Rahima, Aisyah Fani; Aminah, Delima; Wahyuni, Amelia Nur; Munthe, Sahara (The Future of Education Journal, 2026)
Diarrhea remains a significant public health issue, particularly in coastal areas with limited access to clean water and sanitation. Coastal communities tend to have a higher risk of environment-related diseases due to their geographical conditions and daily living habits. Environment-related infectious diseases, such as diarrhea, continue to be a major health concern, especially in coastal regions. The spread of infectious diseases is influenced not only by environmental and sanitation factors but also by local culture and the daily habits of the community. This study aims to describe diarrhea as an infectious disease in relation to clean and healthy lifestyle behaviors (PHBS) and the culture of the coastal community of Cemara Kembar Beach. The research uses a qualitative approach with a descriptive method. Data was collected through in-depth interviews with five informants on December 6, 2025. The results show that the daily habits of the coastal community, such as activities around the beach, the use of well water, and hygiene practices influenced by generational customs, play a role in the occurrence of diarrhea. This study emphasizes that efforts to prevent infectious diseases should take into account the cultural aspects and social behaviors of coastal communities.